Analysis of Tofu Liquid Waste and Rice Washing Water Combination in Microbial Fuel Cell (MFC) System Using Taguchi Experimental Design - Moulita, RA Nurul; Suryani, Faizah (Center for Study and Journal Management FTI UMI, 2024)
Tofu production generates residue in the form of liquid sewage, which is frequently disposed of in sewers. This has the potential to pollute streams and emit a distinct stench that may disturb the neighboring population. Tofu liquid waste can be converted into electrical energy using a Microbial Fuel Cell (MFC) technology. MFC uses the metabolic activity of microorganisms to transform organic chemicals in the substrate into electrical energy. This study will use Taguchi experimental design to provide recommendations for the optimal composition of the substrate usage ratio, incubation period, and addition of bioactivators, as well as their effect on the electrical power produced in MFC system using a combination of tofu liquid waste and rice washing water as the substrate. According to the findings of the research, the parameter with the greatest influence is incubation period (74.81%), followed by addition of bioactivator (19.45%), and substrate ratio (5.46%). The optimal composition is recommended to be incubated for one day with a 5% bioactivator addition and an 80:20 substrate ratio of tofu liquid waste and rice washing water.